The Effect of Integrity And Anti-Fraud Awareness on Fraud Prevention at The Bpkad of Palopo City - Afika Sari Putri; Rifqa Ayu Dasila; Sofyan Samsuddin (LP2M IAIN Palopo, 2025)
Fraudis an act that is not in accordance with the applicable code of ethics and is clearly very dangerous for the Company, As an organizer of government affairs, it is required to be able to organize a transparent and accountable government. The purpose of this study is to test the effect of integrity and anti-fraud awareness on fraud prevention in the BPKAD environment of Palopo City. This study uses a quantitative research type, the sampling method uses a questionnaire distributed online to respondents, Data analysis is carried out using the multiple linear regression method. The results of the study indicate that integrity and anti-fraud awareness have a significant effect on fraud prevention at BPKAD Palopo City. This indicates that the more effective the integrity and anti-fraud awareness are applied, the higher the organization's ability to prevent fraud. Thus, integrity and anti-fraud awareness are also important factors in fraud prevention efforts.